Антидепресивна активність бензиліденових похідних 4-аміно-5-(алкіл-, арил-, гетерил)-1,2,4-тріазол-3-тіонів - Пругло, Євген Сергійович; Пругло, Е. С.; Pruhlo, Ye. S. (Запорізький державний медичний університет, 2018)
Сучасні антидепресанти мають низку недоліків: їм притаманна висока ймовірність розвитку побічних реакцій, недостатня ши¬рота і стійкість терапевтичного ефекту, а також тривалий латентний період дії. Отже, очевидною є потреба у створенні нових препаратів, що поліпшують якість життя, впливають на настрій та є безпечними. Аналіз відомостей фахової літератури показав, що похідні 1,2,4-тріазолу характеризуються вираженою антидепресивною дією, а такі препарати, як тразодон та альпрозалам широко застосовуються в медичній практиці. Мета роботи – дослідження антидепресивної дії похідних 1,2,4-тріазолу й аналіз залежності хімічної будови від цієї фармако¬логічної активності. Матеріали та методи. Пошук антидепресантів у ряду похідних 1,2,4-тріазолу виконували на основі класичної моделі за R. D. Porsolt у модифікації Є. В. Щетиніна. Кожну тварину занурювали на 10 хвилин у посудину, що заповнена водою з температурою 27 °С. Фіксували тривалість активного плавання (енергійні рухи всіма лапами з активним переміщенням), пасивного плавання (слабкі гребки лапами, необхідні для підтримки тіла на плаву) та іммобілізації (відсутність плавальних рухів). Крім того, підраховували число періодів активного плавання різної тривалості і число найкоротших періодів іммобілізації тривалістю до 6 секунд. Обра¬ховували індекс депресивності (ІД) – відношення числа коротких періодів іммобілізації до загального числа періодів активного плавання. Результати досліджень опрацювали сучасними статистичними методами аналізу на персональному комп’ютері з вико¬ристанням стандартного пакета програм Microsoft Office 2013 (Microsoft Excel) Statistica® for Windows 6.0. Розраховували середнє арифметичне (М) та похибку (±m). Статистичну значущість міжгрупових відмінностей за даними експерименту встановлювали за допомогою t-критерію Стьюдента. Результати. Речовини, які дослідили, – бензиліденові похідні 4-аміно-5-(алкіл-, арил-, гетерил)-1,2,4-тріазол-3-тіонів. Індекс де-пресивності при застосуванні флуоксетину, який використовували як еталон, знижувався на 70,92 % (р < 0,05), а при застосуванні прототипу – тразодону – на 76,95 % (р < 0,05). Сполуки 26 і 32 статистично значущо знижували індекс депресивності на 86,66 % та 81,24 % відповідно, що перевищує за активністю препарати порівняння. Основний показник відчаю в щурів – тривалість ім-мобілізації – зменшувався при застосуванні флуоксетину на 73,53 % (р < 0,05), тразодону – на 79,55 % (р < 0,05). Застосовуючи похідні 1,2,4-тріазолу, знижували тривалість іммобілізації сполука 32 – на 89,53 % (р < 0,05), сполука 23 – на 87,05 % (р < 0,05). Висновки. Найактивнішою за результатами досліджень виявилася сполука 32 – 4-(4-(диметиламіно)бензиліденаміно)-5-(2-фтор¬феніл)-4Н-1,2,4-тріазол-3-тіон, який знижував середню тривалість іммобілізації в дослідній групі на 89,53 % та мав доволі низький індекс депресивності (0,34 ± 0,08; р < 0,05). Современные антидепрессанты имеют ряд недостатков: высокая вероятность развития побочных реакций, недостаточная широта и устойчивость терапевтического эффекта, а также длительный латентный период действия. Поэтому очевидна необходимость в создании новых препаратов, которые улучшают качество жизни, влияют на настроение и являются безопасными. Анализ данных специализированной литературы показал, что производные 1,2,4-триазола обладают выраженной антидепрессивной активностью, а такие препараты, как тразодон и альпрозалам широко применяются в медицинской практике. Цель работы – исследование антидепрессивного действия производных 1,2,4-триазола и анализ зависимости химического строения от этой фармакологической активности. Материалы и методы. Поиск антидепрессантов в ряду производных 1,2,4-триазола провели на основе классической модели по R. D. Porsolt в модификации Е. В. Щетинина. Каждое животное погружали на 6 минут в сосуд, заполненный водой с температурой 27 °С. Фиксировали продолжительность активного плавания (энергичные движения всеми лапами с активным перемещением), пассивного плавания (слабые гребки лапами, необходимые для поддержания тела на плаву) и иммобилизации (отсутствие плава¬тельных движений). Кроме того, подсчитывали число периодов активного плавания различной продолжительности и число самых коротких периодов иммобилизации продолжительностью до 6 секунд. Вычисляли индекс депрессивности (ИД) – отношение числа самых коротких периодов иммобилизации к общему числу периодов активного плавания. Результаты исследований обработаны современными статистическими методами анализа на персональном компьютере с использованием стандартного пакета программ Microsoft Office 2013 (Microsoft Excel) и Statistica® for Windows 6.0. Рассчитывали среднее арифметическое (М) и ошибку (±m). Статистическую значимость межгрупповых различий по данным эксперимента устанавливали с помощью t-критерия Стьюдента. Результаты. Исследованные вещества – бензилиден производные 4-амино-5 (алкил-, арил, гетерил)-1,2,4-триазол-3-тиона. Индекс депрессивности при применении флуоксетина снижался на 70,92 % (р < 0,05), при применении тразодона – на 76,95 % (р < 0,05). Соединения 26 и 32 статистически значимо снижали индекс депрессивности на 86,66 % и 81,24 % соответственно, что превышает по активности использованные препараты сравнения. Основной показатель отчаяния у крыс – продолжитель¬ность иммобилизации – уменьшался при применении флуоксетина на 73,53 % (р < 0,05), тразодона – на 79,55 % (р < 0,05). При применении производных 1,2,4-триазола снижали продолжительность иммобилизация соединение 32 – на 89,53 % (р < 0,05), соединение 23 – на 87,05 % (р < 0,05). Выводы. Наиболее активным по результатам исследований оказалось соединение 32 – 4-(4-(диметиламино)бензилиденами¬но)-5-(2-фторфенил)-4Н-1,2,4-триазол-3-тион, который снижал среднюю продолжительность иммобилизации в опытной группе на 89,53 % и имел достаточно низкий индекс депрессивности (0,34 ± 0,08; р < 0,05). The current market for antidepressants has a number of limitations, they have a high probability of development of adverse reactions, have low latitude and stability of the therapeutic effect, and also have a long latent period of action. Therefore, it seems obvious that there is a need to create new drugs that improve the quality of life, affect the mood and are safe. An analysis of literary sources has shown that derivatives of 1,2,4-triazole have a pronounced antidepressant effect and drugs such as Trazodone and Alprozalam are widely used in medical practice. The purpose of this work was to study antidepressant effects of 1,2,4-triazole derivatives and to make analysis of the dependence between chemical structure and pharmacological activity. Materials and methods. The search of antidepressants in the series of 1,2,4-triazole derivatives was performed on the basis of the classical model of R.D. Porsolt in the modification of E.V. Schetynin. Each animal was immersed for 6 minutes in a vessel filled with water at a temperature of 27 °C. The duration of active swimming was fixed (vigorous movements of all paws with active movement), passive swimming (weak bends of the paws necessary to support the body to swim) and immobilization (no swimming motions). In addition, the number of active swimming periods of different lengths and the number of very short immobilization periods of up to 6 seconds were counted. The index of depression (ID) was calculated due to the ratio of the very short periods number of immobilization to the total number of active swimming periods. The research results are processed by modern statistical methods of analysis using personal computer, including the standard program package Microsoft Office 2013 (Microsoft Excel) and Statistica® for Windows 6.0. The average arithmetic mean (M) and standard mean errors (±m) were calculated. The statistical significance of intergroup differences according to the experimental data was established using Student’s t-criterion. To study the dependence of the influence of benzylidene derivatives of 4-amino-5-(alkyl-, aryl-, heteryl)-2,4-dihydro-3H-1,2,4-triazole-3-thione on the duration of passive swimming and the duration of immobilization was carried out by correlation analysis. Results. Benzylidene derivatives of 4-amino-5-(alkyl-, aryl-, heteryl)-1,2,4-triazole-3-thione were used as test substances. The index of depression in the use of fluoxetine decreased to 70.92 % (P < 0.05), and with the use of trazodone to 76.95 % (P < 0.05). Compounds 26 and 32 statistically significantly lowered the index of depression to 86.66 and 81.24 %, respectively, which was higher than the activity of the used comparison drugs. The main indicator of rats despair was the duration of immobilization, decreased to 73.53 % (P < 0.05) and trazodone to 79.55 (P < 0.05) when administered with fluoxetine. When applying 1,2,4-triazole derivatives, the duration of immobilization of compound 32 was reduced to 89.53 % (P < 0.05), and compounds 23 to 87.05 % (P < 0.05). Conclusions. The most active compound according to the results of the study was compound 32, which reduced the average duration of immobilization in the experimental group to 89.53 % and had a rather low index of depression (0.34 ± 0.08, P < 0.05).
Антидепрессивная активность бензилиденовых производных 4-амино-5-(алкил-, арил-, гетерил)-1,2,4-триазол-3-тионов
Antidepressant activity of 4-amino-5-(alkyl-, aryl-, heteryl)-1,2,4-triazole-3-thione benzylidene derivatives
Keywords: антидепрессанты; 1,2,4-триазол; тразодон; antidepressants; 1,2,4-triazole; trazodone; антидепресанти; 1,2,4-тріазол; тразодон